Mycobacterial F420H2-Dependent Reductases Promiscuously Reduce Diverse Compounds through a Common Mechanism - Greening, Chris; Jirapanjawat, Thanavit; Afroze, Shahana; Ney, Blair; Scott, Colin; Pandey, Gunjan; Lee, Brendon M.; Russell, Robyn J.; Jackson, Colin J.; Oakeshott, John G.; Taylor, Matthew C.; Warden, Andrew C. (Frontiers in Microbiology, 2017)
An unusual aspect of actinobacterial metabolism is the use of the redox cofactor F420. Studies have shown that actinobacterial F420H2-dependent reductases promiscuously hydrogenate diverse organic compounds in biodegradative and biosynthetic processes. These enzymes therefore represent promising candidates for next-generation industrial biocatalysts. In this work, we undertook the first broad survey of these enzymes as potential industrial biocatalysts by exploring the extent, as well as mechanistic and structural bases, of their substrate promiscuity. We expressed and purified eleven enzymes from seven subgroups of the flavin/deazaflavin oxidoreductase (FDOR) superfamily (A1, A2, A3, B1, B2, B3, B4) from the model soil actinobacterium Mycobacterium smegmatis. These enzymes reduced compounds from six chemical classes, including fundamental monocycles such as a cyclohexenone, a dihydropyran, and pyrones, as well as more complex quinone, coumarin, and arylmethane compounds. Substrate range and reduction rates varied between the enzymes, with the A1, A3, and B1 groups exhibiting greatest promiscuity. Molecular docking studies suggested that structurally diverse compounds are accommodated in the large substrate-binding pocket of the most promiscuous FDOR through hydrophobic interactions with conserved aromatic residues and the isoalloxazine headgroup of F420H2. LC/MS and GC/MS analysis of derivatized reaction products showed reduction occurred through a common mechanism involving hydride transfer from F420H- to the electron-deficient alkene groups of substrates. Reduction occurs when the hydride donor (C5 of F420H-) is proximal to the acceptor (electrophilic alkene of the substrate). These findings suggest that engineered actinobacterial F420H2-dependent reductases are promising novel biocatalysts for the facile transformation of a wide range of α,β-unsaturated compounds.